Meningkatkan Kemampuan Penjumlahan Deret ke Bawah Melalui Media Cubaritme pada Anak Diskalkulia - Ihsan, Mauzanda; Iswari, Mega (Universitas Negeri Padang, 2023)
Researchers have an interest in raising this issue because it has the aim of helping children in improving students' downward addition skills by using a cubaritme media approach to improve the ability to add downward series in research subjects. This study uses a type of experimental research in the form of Single Subject Research (SSR) with an A-B-A design. The results of data analysis conducted for 15 meetings, where data collection was carried out in two conditions, namely baseline (A) with the acquisition of percentage results of 20%, 40%. 40% and 40%. Then the intervention condition (B) with the acquisition of a percentage of 50%, 50%, 50%, 60%, 70%, 70%, and 70% and the A2 baseline condition with the acquisition of percentage results of 80%, 100%, 100% and 100%. Based on the data obtained from the results of this study, it shows that cubaritme media can improve the ability of downward addition in dyscalculia children at SD 17 Jawa Gadut Padang.